2014
DOI: 10.7554/elife.03821
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 DNA predicts disease progression and post-treatment virological control

Abstract: In HIV-1 infection, a population of latently infected cells facilitates viral persistence despite antiretroviral therapy (ART). With the aim of identifying individuals in whom ART might induce a period of viraemic control on stopping therapy, we hypothesised that quantification of the pool of latently infected cells in primary HIV-1 infection (PHI) would predict clinical progression and viral replication following ART. We measured HIV-1 DNA in a highly characterised randomised population of individuals with PH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
259
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 266 publications
(272 citation statements)
references
References 38 publications
12
259
1
Order By: Relevance
“…S1B in the supplemental material) and other clinical studies (32,33). The magnitude and breadth of HIV-1-specific CD8 T cells determined by ELISpot assays and the proportions of HIV-1-specific CD8 T cells secreting any combination of the analyzed cytokines at the baseline and throughout the study were statistically unrelated to the baseline levels of CD4 T cell-associated HIV-1 DNA or to the relative changes in HIV-1 DNA levels during panobinostat treatment ( Fig.…”
Section: Resultsmentioning
confidence: 89%
“…S1B in the supplemental material) and other clinical studies (32,33). The magnitude and breadth of HIV-1-specific CD8 T cells determined by ELISpot assays and the proportions of HIV-1-specific CD8 T cells secreting any combination of the analyzed cytokines at the baseline and throughout the study were statistically unrelated to the baseline levels of CD4 T cell-associated HIV-1 DNA or to the relative changes in HIV-1 DNA levels during panobinostat treatment ( Fig.…”
Section: Resultsmentioning
confidence: 89%
“…Both FACS and tCD4 cell isolation kits provided tCD4 cells with good purities (medians of 99.8% and 96.1%, respectively). In this comparison, 10 CA HIV-1 DNA and RNA levels adjusted for tCD4 cell purity were highly correlated for the two cell purification methods (CA HIV-1 DNA, r ϭ 0.867; CA HIV-1 RNA, r ϭ 0.770; P Ͻ 0.001) ( Fig. 3A and B; see Fig.…”
Section: Volunteersmentioning
confidence: 99%
“…Prior work showed that CA HIV-1 DNA and RNA remain detectable in most chronically infected individuals despite suppressive ART (7,8). Although the association of CA HIV-1 DNA and RNA levels with the size of the latent HIV-1 reservoir has been called into question (9), recent studies suggest that CA HIV-1 DNA and RNA levels may predict the time to virological rebound after ART cessation and thus may serve as clinically relevant biomarkers (10,11).…”
mentioning
confidence: 99%
“…The time to viral rebound correlates with total viremia during acute infection and with size of latent HIV reservoir at the time of ART discontinuation [67]. This supports that reducing the size of the reservoir may extend the viral free lifespan or time to viral rebound (aka "functional cure"), even if HIV reservoir depleting strategies fail to be complete.…”
Section: Challenges In Hiv Cure: the Hiv Latent Reservoirmentioning
confidence: 54%